A Comparative Study of Ethical and Moral Worldviews in Thai and Chinese Idioms - Tangteekarak, Suwanna; Sanyakul Tan, Siriwan (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2020)
The purposes of this research are 1) to study ethical and moral worldviews in Thai and Chinese idioms, and 2) to compare Thai and Chinese ethical and moral worldviews reflected through idioms. In this qualitative research, Thai and Chinese idioms that reflect ethical and moral worldviews according to the 2011 Thai Qualifications Framework for Higher Education (TQF) in Thai language were specifically analyzed. The research found that Thai idioms reflecting positive attitudes towards work and responsibility contributed the largest proportion (68%), followed by those reflecting honesty, discipline, and respect for organization and social conventions (24%). The third frequent type is Thai idioms reflecting consciousness and habits of prioritizing public interests over one’s own (6%), while Thai idioms reflecting pride in Thai language, Thainess, and positive attitude towards Thai culture made up the smallest proportion (2%). Chinese idioms reflect most frequently the ethical and moral worldviews on honesty, discipline, and respect for organization and social conventions (35%). In second place are idioms that reflect positive attitudes towards work and responsibility (30%), followed by pride in Chinese language, Chineseness, and positive attitudes towards Chinese culture (23%). Occurring the least frequently are Chinese idioms reflecting consciousness and habits of prioritizing public interests over one’s own (12%). The results show that Thai and Chinese people value both 1) positive attitudes towards work and responsibility and 2) honesty, discipline, and respect for organization and social conventions at a high level. However, they value both 1) consciousness and habits of prioritizing public interests over one’s own and 2) pride in Thai/Chinese language, Thainess/Chineseness, and positive attitudes towards Thai/Chinese culture at a low level.